PENGARUH MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XII IIS - Rahmayani, Annisa (Departemen Matematika, 2023)
One of the fundamental aims of studying mathematics is to answer problems. According to the SMA Pembangunan Laboratorium UNP, this ability is still poor and not effectively enabled for growth. Guided inquiry may solve these issues. This research examines whether guided inquiry learning methods help students solve mathematical problems better than standard learning models. Researchers employed a quasi-experiment using a randomized, control-group-posttest only design and random sampling. Conclusion: P-Value = 0.000 from t-test. Data analysis shows that students in class XII IIS SMA Pembangunan Laboratorium UNP who use guided inquiry models solve mathematical problems better than those who use conventional learning models.Keywords– Mathematical Problem Solving Ability, Guided Inquiry, Conventional Learning